Investigando a coerência do termo letramento científico em documentos do Ministério da Educação do Brasil - Rosa, Lucas Cezar Felinto (2022)
Scientific Literacy is a term used for the first time by Paul Hurd, chair associated by the education program at Stanford University on a 1958 paper entitled “Science Literacy: Its Meaning for American Schools”. With that research, many other ones related to scientific education were developed. This dissertation means to character and deliberate two main themes: the context of the foundation on Scientific Literacy term and the many ways to translate it into Brazilian Portuguese Language and the coherence at the Brazilian Education Ministry’s documents, such as: Lei de Diretrizes e Bases da Educação Nacional (LDB); Parâmetros Curriculares Nacionais (PCN+); Diretrizes Curriculares Nacionais da Educação Básica (DCN); e Base Nacional Comum Curricular (BNCC). The method used to do so was a critical analysis of those documents by the full reading of it all, having as indicator the coherence about research of scientific literacy on those documents. As findings, the term was wildly discussed at the USA and in Europe, but was only little discussed in Brazil, where it is possible to find only a few research related to it. Even though, doing research about this subject in Brazil is of major importance, considering that teaching science is fundamental to social, political, educational, and economic development of the society. As a conclusion, it was possible to understand that the term scientific literacy was much debated in the USA and Europe, but little in Brazil, with a smaller amount of research dedicated to this topic. Carrying out more research in the area would be of paramount importance, considering that science teaching is essential for the social, political, scientific, educational and economic development of society. Furthermore, it was possible to notice coherence with scientific literacy term at the Brazilian Education Ministry’s documents analyzed. However, only as quotes along the text and not as a plan to be executed in education